Gli scaffold in medicina rigenerativa - Trinchese, Giovanni Felice; Calabrese, Emanuele; Calabrò, Giampiero; Lisanti, Francesco (Lo Scalpello - Journal, 2019)
SCAFFOLDS IN REGENERATIVE MEDICINE Scaffolds are artificial structures capable of supporting the formation of three-dimensional tissue. Their use in the orthopaedic field appears to be a powerful weapon for treating numerous diseases. Unfortunately, despite great efforts in the realisation of the ideal scaffold, their use in clinical practice is still limited due to the many characteristics that it must possess. The purpose of this review was to provide a critical perspective of scaffolds in the orthopaedic field, highlighting their main characteristics and the methods for their production.